Highly Stretchable Resistive Pressure Sensors Using a Conductive Elastomeric Composite on a Micropyramid Array. (17th February 2014) - Choong, Chwee‐Lin; Shim, Mun‐Bo; Lee, Byoung‐Sun; Jeon, Sanghun; Ko, Dong‐Su; Kang, Tae‐Hyung; Bae, Jihyun; Lee, Sung Hoon; Byun, Kyung‐Eun; Im, Jungkyun; Jeong, Yong Jin; Park, Chan Eon; et al.
<x xml:space="preserve">Abstract</x> A stretchable resistive pressure sensor is achieved by coating a compressible substrate with a highly stretchable electrode. The substrate contains an array of microscale pyramidal features, and the electrode comprises a polymer composite. When the pressure‐induced geometrical change experienced by the electrode is maximized at 40% elongation, a sensitivity of 10.3 kPa−1 is achieved. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>